The Effect of Healthy Drinks (Dragon Fruit and Soybean) on Hemoglobin Changes in Third Trimester Pregnant Women To Prevent Stunting In Infants - Yuniza, Yuniza; Ginanjar, Marwan Riki; Ulaa, Mar’atun; Rizona, Firnaliza (Eduvest - Journal of Universal Studies, 2025)
Nutritional deficiency during pregnancy can lead to anemia, which affects fetal growth and increases the risk of stunting in infants. Natural interventions using nutrient-rich foods may provide safe alternatives to address hemoglobin deficiency in pregnant women. Objective: This research aims to evaluate the effect of healthy drinks containing dragon fruit and soybean on hemoglobin level changes in third-trimester pregnant women as a preventive measure against infant stunting. This quantitative research employed a pre-experimental design with a one-group pretest-posttest approach. The sample was selected using a non-probability sampling technique with a total of 24 respondents at the Palembang City Health Center from February to April 2024. This research used instruments for measuring hemoglobin levels and SOPs for administering healthy drinks. The analysis was carried out using the paired samples t-test. The average hemoglobin (Hb) level before administration of red dragon fruit juice in third-trimester pregnant women was 10.58 g/dL, while the average hemoglobin (Hb) level after administration of red dragon fruit juice in third-trimester pregnant women was 10.87 g/dL, with a p-value of 0.000 < 0.05. There was a significant effect of healthy drink administration on hemoglobin levels in third-trimester pregnant women between before and after the intervention.